2020
DOI: 10.1049/hve.2019.0124
|View full text |Cite
|
Sign up to set email alerts
|

Development and pattern identification of end‐winding discharge under effect of relative humidity and temperature for HV motors

Abstract: During operation of high voltage (HV) motors, different types of discharges, e.g. surface discharge, corona discharge and bar‐to‐bar discharge can occur at the same time, increasing the difficulty of partial discharge (PD) sources determination and PDs pattern identification. In this study, the end‐winding of a 10 kV motor coil was artificially aged and the related PD was measured. The initiation and variation of different PDs under multi‐factor stresses were studied. The localised fingerprints coexisting with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Further, the author has proposed a cloud-based storage system to store the monitored data. Kang et al [18] (2020) have proposed the detection method of high voltage motors during end-to-end winding faults. Further, the authors have proposed an online monitoring partial discharge identification method to detect and identify the pattern of faults under different temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Further, the author has proposed a cloud-based storage system to store the monitored data. Kang et al [18] (2020) have proposed the detection method of high voltage motors during end-to-end winding faults. Further, the authors have proposed an online monitoring partial discharge identification method to detect and identify the pattern of faults under different temperature conditions.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, several researchers have proposed the IoT-based condition monitoring of induction machines [12][13][14][15][16][17][18][19][20]. Jeyalakshmi et al [13] (2020) have developed a smart motor condition monitoring system to monitor the vibration and temperature of the motor using MyRio software platform.…”
Section: Literature Surveymentioning
confidence: 99%
“…More references about the PRPD for surface discharge including surface discharge on Epoxy Resin, the solid insulation used in this paper, can be found in literature, e.g. [37], [38], [39], [40], [41], [42], [43], [44], [45], [46]. Indeed, by increasing the applied voltage, the discharge number and discharge amplitude in both positive and negative half-cycles will increase accordingly for both antenna and HFCT sensor.…”
Section: ) Partial Discharge Waveform Amplitude Measurementmentioning
confidence: 99%
“…It was then concluded that the acid gas environment can effectively suppress the occurrence of corona discharge, and the higher the humidity ratio, the less likely corona discharge to occur [113]. Kang et al studied the effect of relative temperature on corona discharge, where the effect of temperature on corona discharges was confirmed [16].…”
Section: ) Defect In Slot Exitmentioning
confidence: 99%